Nursing Care for Palliation: Improvement of the Quality of Life in Patients with Chronic and Terminal Diseases - Bandar Moftah Alfahmi, Mazin Saleh Alheag, AwadMonawer Albishri, Abeer Mohammad Aladwani, Mareae Abdullah Lihayni,; Ali Abdrahman Alzahrani, ‏Ahmed Hamed Mohammed Alsuhimi, Etab Ahmed Sahlooli, Reema Ali Etuoody, Ebtehag Hamzah Alshekhay, (Journal of International Crisis and Risk Communication Research, 2024)
Palliative nursing care is crucial in healthcare systems to improve the quality of life for patients with chronic and terminal illnesses. This paper explores pain management, psychological and emotional support, and addressing social and spiritual needs. Evidence-based nursing interventions ensure comfort, dignity, and holistic well-being. New developments in palliative care include digital tools, personalized care models, and interdisciplinary collaboration. Patient- and family-centered approaches can improve caregiver satisfaction and reduce emotional distress. Challenges faced by palliative nurses include workforce shortages, resource constraints, and ethical dilemmas. The study recommends leveraging technology, promoting targeted training programs, and developing supportive policies for health professionals. The findings highlight the transformative potential of nursing care in alleviating suffering and enhancing quality of life.